Cultural Nationalism: The Last Resort of Scoundrels - Eric Jones (Queen's University, Department of Economics, 2006)
This is the text of the Chancellor Dunning Trust Lecture as it was delivered on Oct. 4, 2006.
Keywords: A13; F10; 330; Culture; Nationalism; Protectionism; Collectivism